Purcell - Westrup, Jack Allen 1904-1975 (London Dent, 1975)
In this classic study, reissued on the 300th anniversary of Purcell's death, Sir Jack Westrup drew on documentary evidence from the Court, Westminster Abbey, and other sources to give a vivid account of Purcell's life in seventeenth-century London. The range of Purcell's compositions is also fully covered, from small-scale pieces to music for state occasions and works for the Restoration stage.
Originally published in 1937
Keywords: Purcell, Henry -- 1659-1695; 17th Century (1601-1700); Composer; Biography; United Kingdom